2019
DOI: 10.1093/sf/soz014
|View full text |Cite
|
Sign up to set email alerts
|

Are Parental Relationships Improved if Fathers Take Time Off of Work After the Birth of a Child?

Abstract: Research has begun to examine the consequences of paternity leave, focusing primarily on whether paternity leave-taking increases father involvement. Yet, other consequences of paternity leave-taking have not been considered using U.S data. This study uses longitudinal data from the Fragile Families and Child Wellbeing Study to examine whether fathers' time off from work after the birth of a child is associated with relationship quality, relationship support, and coparenting quality. We also consider whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 60 publications
3
32
1
Order By: Relevance
“…Although a larger percentage believe mothers should have access (82%), it is noteworthy that a strong majority (69%) also favor paid paternity leave (Horowitz et al, 2017). And there are reasons to believe that more generous paternity leave would promote more egalitarian family arrangements: fathers who take time off after the arrival of a new child spend more time on housework and caregiving over the long term, develop a deeper sense of responsibility and proficiency in parenting skills, experience the transition to parenthood more similarly to mothers, and experience better relationship and coparenting quality than their counterparts who do not take such leave (Patnaik, 2018;Petts & Knoester, 2019;Rehel, 2014).…”
Section: Equality: An Increasingly Popular Family Paradigmmentioning
confidence: 99%
“…Although a larger percentage believe mothers should have access (82%), it is noteworthy that a strong majority (69%) also favor paid paternity leave (Horowitz et al, 2017). And there are reasons to believe that more generous paternity leave would promote more egalitarian family arrangements: fathers who take time off after the arrival of a new child spend more time on housework and caregiving over the long term, develop a deeper sense of responsibility and proficiency in parenting skills, experience the transition to parenthood more similarly to mothers, and experience better relationship and coparenting quality than their counterparts who do not take such leave (Patnaik, 2018;Petts & Knoester, 2019;Rehel, 2014).…”
Section: Equality: An Increasingly Popular Family Paradigmmentioning
confidence: 99%
“…Researchers are increasingly recognizing the usefulness of paid parental leave. For example, there is evidence that paid parental leave helps to maintain similar levels of household income during spells of caregiving needs surrounding a birth, supports mothers' continued labor force participation after a birth, and helps to alleviate work-family conflicts (Baum and Ruhm 2016;Byker 2016;Gault et al 2014;Petts and Knoester 2019;Stancyzk 2016). Moreover, scholars find that paid parental leave is associated with health benefits for both mothers and infants (Aitken et al 2015;Bullinger 2019;Gault et al 2014;Tanaka 2005).…”
Section: Attitudes About Paid Parental Leave In the Usmentioning
confidence: 99%
“…Studies show that paternity leave policies increase take‐up of leave (Bartel, Rossin‐Slater, Ruhm, Stearns, & Waldfogel, ; Ekberg, Eriksson, & Friebel, ), affect earnings (Rege & Solli, ), and to a lesser extent, increase men's housework (Kotsadam & Finseraas, ). In the United States, a few studies have found that paternity leave is associated with greater parenting engagement (Petts & Knoester, ; Pragg & Knoester, ; Seward, Yeatts, & Zottarelli, ) and coparenting (Petts & Knoester, ), especially if that leave was 2 weeks or greater (Huerta et al, ; Nepomnyaschy & Waldfogel, ; Petts & Knoester, ). Outside of the United States, paternity leave has been linked with greater fathering and child care (Bunning, ; Bunning, 2015b; Haas & Hwang, ; Schober, ; Tanaka & Waldfogel, ), but also weak links (Hosking, Whitehouse, & Baxter, ), and no effects on child care (Ekberg et al, ; Kluve & Tamm, ; Patnaik, ; Rieck & Telle, ; Ugreninov, ).…”
Section: Prior Researchmentioning
confidence: 99%